Allometrically-Adjusted Morphometric Measurements and Morphological Differentiation Between Two Closely Related Loaches Nemacheilus chrysolaimos and Nemacheilus fasciatus) - Bahtiar Arddun Asyafiq; Agung Budiharjo; Puguh Karyanto (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to morphologically distinguish the two closely related loaches, N. chrysolaimos and N. fasciatus using an integrated approach that combines allometrically-adjusted morphometrics measurements, meristic counts, and observable morphological features. Loaches samples were collected from six river systems representing the Progo, Serayu, and Bengawan Solo watersheds in Central Java and the Special Region of Yogyakarta. Morphometric measurements were adjusted using Elliott formulation to reduce allometric bias prior to Principal Component Analysis (PCA). The value of PC1 and PC2 accounting for 42.31%. The results shows that. N. chrysolaimos showed greater caudal peduncle depth and dorsal fin length, whereas N. fasciatus was more strongly associated with dorsal fin height and caudal fin length. Meristic characters provided additional evidence, with the examined specimens of N. chrysolaimos showing higher than N. fasciatus for lateral-line scales (198 vs 156), transverse scale rows (14 vs 10), preorsal scales (57 vs 39), and circumpeduncular scales (27 vs 18), as well as dorsal (10 vs 9) and pecotral (9 vs 7) soft raysi.e. body color pattern, mouth shape and barbel orientation also distinguished the species. These findings demonstrate that combined morphometric, meristic, and morphological characters provide reliable diagnostic evidence for distinguishing between the two species in Java.